The influence of Unified Power Flow Controller to increase the value of Available Transfer Capability on transmission system Java – Bali, Indonesia. Issue 1 (October 2021) - Siahaan, D P S; Soebagio, A; Widodo, B; Stepanus, S; Sihite, E B O
Abstract: Industrial growth and population in Indonesia led to an increase in demand for electricity. It needs a device that can perform a voltage correction profile online so that power will flow through transmission line. TJBTB ( Transmisi Jawa Bagian Timur dan Bali ) conditions before the installation of UPFC ( Unified Power Flow Controller ), the power supply received by the load is not 100% obtained from plants in the region, for example the Paiton power plant. In this research, the method used is with the help of MATLAB R2014a simulation by designing a 500 kV transmission system configuration and the placement of the UPFC found in regional IV namely East Java - Bali. From the simulation results, showing that there was a change in power flow when placing the UPFC. The right location is the West Surabaya - Gresik channel. On the Ngimbang bus there is a change in active power which before using UPFC by 1612 MW to 2208 MW after using UPFC, an increase in active power was 36.97%. The UPFC can fulfill all these functions and thereby meet multiple control objectives by adding the injected voltage with appropriate amplitude and phase angle, to the terminal voltage v.